Do direct R&D subsidies lead to the monopolization of R&D in the economy? - Dirk Czarnitzki; Bernd Ebersberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper explores the impact of R&D subsidies on the concentration of R&D in an economy. First, governments are often criticized of subsidizing predominantly larger firms and thus contribute to persistence of leadership in markets and higher barriers to entry, and, hence, reduced competition eventually. Second, theoretical literature, such as endogenous growth literature, has also shown that governmental intervention in the market for R&D affects the distribution of R&D which finally affects product market concentration. We test the relationship between R&D subsidies and R&D concentration employing treatment effects models on data of German and Finnish manufacturing firms. The data and estimations allow calculating concentration indices for the population of firms for both the actual situation where some selected companies receive R&D subsidies and the counterfactual situation describing the absence of subsidies. We find that R&D subsidies do not lead to higher concentration of R&D. On the contrary, we even find that R&D concentration is significantly reduced because of subsidies. This result may be attributed to the fact that technology policy maintains special funding schemes for small and medium-sized companies. The fact that the larger companies benefit from a higher likelihood of a subsidy receipt is offset by the phenomenon that smaller firms may be completely deterred from any R&D activity if they would not receive governmental support.
Keywords: O31; O32; O38; 330; R&D Concentration; R&D Subsidies; Treatment Effects; Policy Evaluation; Forschungs- und Technologiepolitik; Subvention; Wirkungsanalyse; Industrielle Forschung; Wirtschaftskonzentration; Klein- und Mittelunternehmen; Deutschland; Finnland